Pengaruh Bimbingan Belajar terhadap Kesulitan Belajar Matematika Siswa Kelas X MA Palapa Nusantara NW Selebung - Laili, Husnul (Lembaga Yasin AlSys, 2022)
This study aims to determine the effect of tutoring on the learning difficulties of class X students of MA Palapa Nusantara NW Selebung. The subject that is the focus of the research is Mathematics. This research is a quantitative research with experimental design. The subjects of this study were students of class X IPS MA Palapa Nusantara NW Selebung. Data collection techniques using questionnaires, documentation, interviews, and observations. The implementation of tutoring given to students who have learning difficulties is effective in improving the learning outcomes of class X IPS MA Palapa Nusantara NW Selebung for the 2021/2022 academic year. This can be seen from the acquisition value in the statistical analysis of 2.985. This value is greater than the ttable value at the 5% significance level, which is 1.658 and at the 1% significance level, it is 2.358. Therefore, the implementation of tutoring is effective in overcoming student learning difficulties, especially in Mathematics.